Examining local traditional food entrepreneurs in selangor and sabah States during covid 19 pandemic - Adilah Md Ramli; Mazni Saad; Mohd Shazali Md Shariff; , Joko Sulistyo (Association of Malaysian Environment-Behaviour Researchers, 2023)
The study aims to explore local entrepreneurs’ profile criteria during covid 19 pandemic in Sabah and Selangor states. Two (2) themes have been identified for this study which are 1) Food category and 2) Business criteria. Twenty (20) informants from selected business categories are being identified and interviewed using a semi-structured question and online video and phone recording due to the Covid 19 pandemic. The finding shows that entrepreneurs from both states share similarities in food categories and customer backgrounds. They also implement technology such as online delivery applications to sustain their business during the Covid-19 pandemic.